Responding to a diagnosis of localized prostate cancer - Wall, David; Kristjanson, Linda; Fisher, C.; Boldy, Duncan; Kendall, Garth (Lippincott Williams & Wilkins, 2012)
Background: Men experience localized prostate cancer (PCa) as aversive and distressing. Little research has studied the distress men experience as a normal response to PCa, or how they manage this distress during the early stages of the illness. Objectives: The objective of this study was to explore the experience of men diagnosed with localized PCa during their first postdiagnostic year. Methods: This constructivist qualitative study interviewed 8 men between the ages of 44 and 77 years, in their homes, on 2 occasions during the first 3 postdiagnostic months. Individual, in-depth semistructured interviews were used to collect the data. Results: After an initial feeling of shock, the men in this study worked diligently to camouflage their experience of distress through hiding and attenuating their feelings and minimizing the severity of PCa. Conclusions: Men silenced distress because they believed it was expected of them. Maintaining silence allowed men to protect their strong and stoic self-image. This stereotype, of the strong and stoic man, prevented men from expressing their feelings of distress and from seeking support from family and friends and health professionals. Implications for Practice: It is important for nurses to acknowledge and recognize the normal distress experienced by men as a result of a PCa diagnosis. Hence, nurses must learn to identify the ways in which men avoid expressing their distress and develop early supportive relationships that encourage them to express and subsequently manage it.